Microcommunities In Enterprises - Challenges Resulting From The Formation Of Natural Divisions In The Working Environment - Przemyslaw Dembowski (Communications of International Proceedings, 2022)
The article is the result of the author's research on new forms of human resource management. The subject of the article is a short presentation of the evolution of forms of human resource management and new challenges faced by the management staff as a result of these changes. Author focused on one of the increasingly serious problems called horizontal mobbing, which left to itself constitute a serious threat to the proper functioning of the workers' society. First of all, there were analyzed the reasons for this phenomenon, the sources of which author views in the same human characteristics that are responsible for the formation and functioning of social groups. In the following, there is an attempt to find possible solutions to this problem through analogous activities of various institutions whose aim is to combat and eliminate the effects of social exclusion.
Keywords: Employee community; mobbing; reference group; harassment; social exclusion.